Uniform Expression and Relatively Small Position Effects Characterize Sister Transformants in Maize and Soybean - Betts, Scott D.; Basu, Sutirtha; Bolar, Joy; Booth, Russ; Chang, Shujun; Cigan, A. Mark; Farrell, Jeffry; Gao, Huirong; Harkins, Kristi; Kinney, Anthony; Lenderts, Brian; Li, Zhongsen; et al. (Frontiers in Plant Science, 2019)
Development of transgenic cell lines or organisms for industrial, agricultural, or medicinal applications involves inserting DNA into the target genome in a way that achieves efficacious transgene expression without a deleterious impact on fitness. The genomic insertion site is widely recognized as an important determinant of success. However, the effect of chromosomal location on transgene expression and fitness has not been systematically investigated in plants. Here we evaluate the importance of transgene insertion site in maize and soybean using both random and site-specific transgene integration. We have compared the relative contribution of genomic location on transgene expression levels with other factors including cis-regulatory elements, neighboring transgenes, genetic background and zygosity. As expected, cis-regulatory elements and the presence/absence of nearby transgene neighbors can impact transgene expression. Surprisingly, we determined not only that genomic location had the least impact on transgene expression compared to the other factors that were investigated, but that the majority of insertion sites recovered supported transgene expression levels that were statistically not distinguishable. All 68 genomic sites evaluated were capable of supporting high level transgene expression, which was also consistent across generations. Furthermore, multi-location field evaluation detected no to little decrease in agronomic performance as a result of transgene insertion at the vast majority of sites we evaluated with a single construct in five maize hybrid backgrounds.